Student perceptions of multilingual learning and teaching in two faculties at a South African university - Kluyts, Marike; De Klerk, Danie; Dlamini, Phiwokuhle; Padayachee, Kershree (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
Language can create multifaceted and complex dilemmas for higher education stakeholders, as language remains a gateway to epistemological access. This is especially true in a multilingual country like South Africa, where the language of learning and teaching (LoLT) at universities is typically English. Nevertheless, many South African universities have adopted multilingual language policies. The University of the Witwatersrand (Wits) implemented its current language policy in 2015. In this article, the authors share findings from a cross-faculty multilingualism research project, focusing on the perceptions and insights registered students had of the Wits Language Policy. The aim is to inform and support continuing policy implementation strategies that are appropriate and aligned to students’ learning needs and preferences. Data was collected from registered students in the Faculties of Science and Commerce, Law and Management, using a questionnaire. The findings suggest that not all students know of the institution’s Language Policy or what the official Wits LoLTs are. There also appears to be a preference for English as the language of teaching in formal, lecturer-led spaces, and more openness to multilingualism in less formal, peer-to-peer learning interactions. The authors conclude by briefly discussing the implications of these findings for learning and teaching, before addressing limitations and outlining plans for further research.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 3, Volume 8, 2024 Special Issue
Keywords: Language policy; Multilingualism; Student learning; Translanguaging; Multilingual education; Student learning communities; Translanguaging (Linguistics); Language policy